Effect of spironolactone on monocyte subsets in atrial fibrillation: IMPRESS-AF randomised controlled trial - Farhan Shahid; Eduard Shantsila; Alena Shantsila; Gregory Y H Lip (Scientific Reports)
Abstract Background Monocyte subsets differentially influence pathophysiology of heart failure and atrial fibrillation (AF) through inflammation, fibrosis, and angiogenesis. Spironolactone has antifibrotic properties. This study investigated the effect spironolactone on monocyte subsets and monocyte effects for peak oxygen consumption (peakVO2), diastolic function and brain natriuretic peptide (BNP) in the IMPRESS-AF randomised controlled trial population (2-year treatment with spironolactone 25 mg vs placebo). Methods CD14++CD16-CCR2+(Mon1), CD14++CD16+CCR2+(Mon2) and CD14+CD16++CCR2-(Mon3) monocyte subsets were analysed by flow cytometry and compared between spironolactone and placebo groups at 12 months and 24 months after randomisation. PeakVO2, diastolic function (echocardiographic E/'e) and BNP were measured at baseline and 24 months. Linear regression was used to assess the effects of monocytes on the outcomes (Python 3.10 modules). Results Monocyte data were available in 225 (90%) IMPRESS-AF patients (age 72[67-77], 78% male). At 12-month the spironolactone group had fewer Mon3 (50[36-74] vs 60[44-90] cells/microL, p=0.02), and lower CD14 expression on Mon1 (1.37[1.17-1.59] vs 1.48[1.24-1.70], p=0.04); no difference remained by 24 months (p>0.05). A high 12-month Mon1 count independently predicted lower E/e’ at 24 months (p=0.02). Conclusions Spironolactone temporarily reduced proinflammatory monocyte markers (Mon3 count and CD14 expression on Mon1). Mon1 may have a positive effect on diastolic dysfunction in AF.